Think today: an ethical responsibility of philosophy (Cultura Económica, 2019)
Thinking about the current historical situation implies, for the author, a continuous historical interpretation and discernment. Within Ricoeur’s hermeneutics, such a reading could be related to textual hermeneutics assuming that reality can be interpreted as a text embedded of meaning. This explanatory method will lead to the production of various interpretations, encouraging an interdisciplinary and intercultural dialogue.
Keywords: hermeneutics; discernment; ethics; historical situation; philosophical thought